If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2x + 1) = 2x + -6x Reorder the terms: 6(1 + 2x) = 2x + -6x (1 * 6 + 2x * 6) = 2x + -6x (6 + 12x) = 2x + -6x Combine like terms: 2x + -6x = -4x 6 + 12x = -4x Solving 6 + 12x = -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 6 + 12x + 4x = -4x + 4x Combine like terms: 12x + 4x = 16x 6 + 16x = -4x + 4x Combine like terms: -4x + 4x = 0 6 + 16x = 0 Add '-6' to each side of the equation. 6 + -6 + 16x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 16x = 0 + -6 16x = 0 + -6 Combine like terms: 0 + -6 = -6 16x = -6 Divide each side by '16'. x = -0.375 Simplifying x = -0.375
| -13s-5+5s=11s+2(-11s-16) | | 312.50=a+.25 | | 3y^2+21y=0 | | n=4+(n+1)(-5) | | 2s=2s+6 | | 4(2x+7)=-30+26 | | 6x+19=63 | | -300=5(8a+4) | | -35x+42=-29x-6 | | 0=4x^2+12x+13 | | -8+4x=2x+18 | | -2(2x-9)-7x=30 | | 2(20y-20)=-5(20-12y) | | -5(x-4)-25=-5 | | -4x-4=-2x+12 | | 3p-15+3p=-27 | | 7X+10y=655 | | 900x+45= | | 8x-18=6x+2 | | 9=12t | | 110+t^2=190+2t | | -6+2x=8+3x | | -7(5n-16)=-7n | | t+75=4t | | b+9=4b | | -11+5x=4+6x | | 2(4x-3)-8=4(4-2x) | | s+81=2s | | -20h=-7(4h+20)-12 | | 90-2x=-5+3x | | x-40=-5x+50 | | -2.25(x-1.5)(x-6)=0 |